A new species of genus Dryophilocoris Reuter (Hemiptera: Heteroptera: Miridae: Orthotylinae) from South Korea, with a key to Korean species - Cho, Young Jae; Kwon, Yong Jung (Zootaxa, 2011)
Dryophilocoris Reuter 1875 is a small genus of the Palaearctic mirid subfamily Orthotylinae, with 12 described species in the world (Kerzhner & Josifov, 1999; Yasunaga, 1999). Most species in this genus are distributed in northeastern Asia, except for three European species. The members of this genus can be easily distinguished by a combination of the following: (1) body elongate, parallel-sided; (2) a vertex with transverse carina basally; (3) eye almost contiguous to the pronotum; (4) anteriorly constricted pronotum divided into two (anterior and posterior) lobes; (5) an impunctate pronotum and shallowly punctate hemelytra with blackish short pubescences; (6) vesica with 3 sclerites.